Artifacts of thinking : reading Hannah Arendt's Denktagebuch - Berkowitz, Roger 1968- HerausgeberIn; Storey, Ian HerausgeberIn; Arendt, Hannah 1906-1975 ErwähnteR (Fordham University Press, 2017)
Reconciling oneself to the impossibility of reconciliation : judgment and worldliness in Hannah Arendt's politics / Roger Berkowitz -- On the truth-and-politics section in the Denktagebuch / Ursula Ludz -- "By relating it" : on modes of writing and judgment in the Denktagebuch / Thomas Wild -- Thinking in metaphors / Wout Cornelissen -- The task of knowledgeable love : Arendt and Portmann in search of meaning / Anne O'Byrne -- Vita passiva : love in Arendt's Denktagebuch / Tatjana Noemi Tömmel -- America as exemplar : the Denktagebuch of 1951 / Tracy B. Strong -- "Poetry or body politic" : natality and the space of birth in Hannah Arendt's thought diary / Jeffrey Champlin -- Facing the end : the work of thinking in the late Denktagebuch / Ian Storey